THE FACTORS OF GREEN MARKETING AFFECTING CONSUMER PURCHASE INTENTION IN LATVIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
Remarkably, the percentage of environmentally friendly practices used in marketing is growing. The understanding of how to use environmentally friendly practices is the primary cause for this high grade. The vast majority of customers have a good understanding of green technology and the beneficial influence that they have on the environment. According to the findings of a recent research, customers' awareness of environmental concerns may be increased via eco-friendly marketing strategies. Consumers in Latvia have placed a considerably greater emphasis on environmentally responsible practices as a means of marketing. Research goal: to identify the factors of green marketing affecting consumer purchase intention in Riga, Latvia.  Research method: a survey. For the purpose of processing the data in the SPSS environment, the following methods were utilized: descriptive statistical analysis, analysis of reliability, analysis of factors, analysis of regression. Main findings: due to the very fluid and complicated nature of the current business climate, this study investigates the facts and realities surrounding green customers.